303 Identification of candidate genes related to temperament in Brahman cattle. (5th December 2019) - Paredes-Sanchez, Francisco A; Casas, Eduardo; Parra-Bracamonte, G M; Arellano-Vera, W; Riley, David G; Welsh, Thomas H; Sifuentes-Rincón, A M; Randel, Ronald D
Abstract: The objective of this study was to identify genomic regions and genes associated with beef cattle temperament. Temperament, measured as exit velocity (EV; m/s), was recorded in 1, 370 Brahman cattle from Texas A&M AgriLife Research at Overton, TX. We identified two groups of temperament-contrasting animals. Cows were calm if their EV of 0.16–3.41 m/s and bulls if their EV was 0.4–3.12 m/s (n-119). Cows were temperamental if their EV was 3.55–7.66 m/s and bulls if their EV was 3.13–10.83 m/s (n = 79). The 198 animals were genotyped using the GGP-HD-150K chip. 139, 376 SNPs were evaluated for association with temperament. 13 SNP′s were associated with EV (P < 4.0E-05). The SNPs GABRG2-26484, NRXN3-26436 and TBX20-191081 are located in introns of the GABRG2, NRXN3 and TBX20 genes, respectively. The GABRG2 gene encodes a GABA receptor, the major inhibitory neurotransmitter in the mammalian brain. The NRXN3 gene encodes receptor proteins related to chemical transmission at synapses. TBX20 is a member of the T-box transcription factor family expressed in the developing stages of heart, limbs, eye and ventral neural tube. To test the effect of these 3 SNP′s on EV, Pen-Score and Temperament-Score, a general linear model was fitted including the fixed effects of sex of calf and year of birth, and the individual effect of the 3 SNPs. The marker TBX20-191081 was associated with the three traits evaluated (P < 0.01), where the GG genotype was associated with the calmest temperament. The GG genotype had a significant effect on EV (P < 0.0001) that was 1.35 and 1.95 m/s slower than AG and AA, respectively. For TS, the GG genotype had a TS that was 1.41 and 1.24 DS less than those of the AA and GA genotypes. Our study indicates that genetic control of cattle temperament has a wide network of genes with divergent functions and genetic background specificity.